PENERAPAN MODEL MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK TENTANG GETARAN DAN GELOMBANG - Eka Fittriyani; Edy Tandililing; Hamdani Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstrak This study aims to improve students’ learning outcomes on vibration and wave material by applying the Make A Match model. The form of the study is a pre-experimental design with a group pre-test post-test. This study is conducted at SMP Negeri 1 Sungai Raya that involved 32 students in the VIII G class. Data collection instrument in the form of 10 multiple choice questions and 4 essay questions. The result shows that the increase of students’ learning outcomes after the implementation of the Make A Match model, it is proven from the acquisition of the average score of each material indicator with an increment of 22.74%. Wilcoxon Test results obtained an Asymp.sig score of 0,000 <0.05, thus Ha is accepted, which means there are differences in students’ learning outcomes before and after the Make A Match model is applied. The application of the Make A Match model is effective for improving students’ learning outcomes related to the vibrations and waves with 1.47 value (relatively high). The Make A Match learning model is expected to be used as an alternative in efforts to improve student learning outcomes. Keyword : Application, Learning Outcomes, Make A Match, Vibration and Waves